TRANSFORMASI KEARSIPAN PENDIDIKAN DASAR: PERSEPSI DAN PENGALAMAN STAF TATA USAHA SD SWASTA ANNYSA DALAM PENGGUNAAN SISTEM ARSIP DIGITAL DAN MANUAL - Shinta, Dewi; Prd, Intan Amalia Putri; Ramadhani, Jihan Aulia; Abdillah, Mhd Rizki; Mardiah, Raudhatul; Sembiring, Ummi Auliyah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2025)
Every organization, be it a government agency, private institution or educational institution such as elementary school, must have administrative activities that are the basis for running daily operations. Administration related to correspondence or archiving of important documents belonging to the school or office. In the digital era, many agencies and schools have begun to switch from manual archive systems to digital archive systems. However, not all schools or offices have implemented the digitalization system optimally. Agencies or schools that have switched or implemented this digital archive system must have their own experiences and perceptions regarding this digital archive system. And of course they already know the advantages and disadvantages of both archive systems.